2011
DOI: 10.3109/1354750x.2011.622789
|View full text |Cite
|
Sign up to set email alerts
|

Serum omentin-1 levels are inversely associated with the presence and severity of coronary artery disease in patients with metabolic syndrome

Abstract: Serum omentin-1 might be a potential biomarker to predict the development and progression of CAD in MetS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 17 publications
0
48
0
2
Order By: Relevance
“…De Souza et al (26) showed that omentin gene expression was decreased with obesity and decreased omentin levels were associated with increasing obesity and insulin resistance. Furthermore, serum omentin-1 levels were shown to be inversely associated with the presence and severity of coronary artery disease in patients with metabolic syndrome (27). This data showed that there may be a putative role of human omentin gene missense variation in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 71%
“…De Souza et al (26) showed that omentin gene expression was decreased with obesity and decreased omentin levels were associated with increasing obesity and insulin resistance. Furthermore, serum omentin-1 levels were shown to be inversely associated with the presence and severity of coronary artery disease in patients with metabolic syndrome (27). This data showed that there may be a putative role of human omentin gene missense variation in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 71%
“…In patients with metabolic syndrome, omentin-1 levels inversely correlated with the presence and angiographic severity of CAD (ref. 11 ). Another interesting new observation in our study is that omentin-1 levels in CAD patients did not differ between patients with acute myocardial infarction and patients in the chronic phase of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Także Ismail i Mohamed zwrócili uwagę na mniejsze stężenie omentyny u chorych na łuszczycę. Ze względu na jej protekcyjną rolę w przeciwdziałaniu tworzeniu się blaszki miażdży-cowej w naczyniach wieńcowych i w rozwoju innych zaburzeń naczyniowych wynikających z otyłości badacze zasugerowali, że jej małe stężenie u pacjentów z łuszczycą może się przyczyniać do częstszego występowania powikłań naczyniowych u tych chorych [41,42]. Przedstawione badania wykazują, że małe stężenie omentyny może odgrywać rolę w powstawaniu stanu zapalnego, co z kolei może powodować rozwój zarówno łuszczycy, jak i towarzyszących jej zaburzeń metabolicznych i naczyniowych.…”
Section: Vaspinunclassified
“…Ismail and Mohamed have also highlighted lower concentrations of omentin in psoriatic patients. Taking into account the protective role of omentin both in the prevention of atheromatous plaque deposition in coronary vessels and the development of other obesity-related vascular disorders, the researchers have suggested that low omentin levels in patients with psoriasis may be a factor contributing to a greater incidence of vascular complications in this patient group [41,42]. The studies presented above suggest that a low concentration of omentin may be a factor in the emergence of inflammation, which in turn may contribute both to the development of psoriasis and metabolic and vascular disorders accompanying it.…”
Section: Omentynamentioning
confidence: 99%